2022
DOI: 10.1109/led.2022.3185781
|View full text |Cite
|
Sign up to set email alerts
|

Steep Switching Si Nanowire p-FETs With Dopant Segregated Silicide Source/Drain at Cryogenic Temperature

Abstract: Fully silicided source/drain Si gate-all-around (GAA) nanowire (NW) p-FETs with NW diameter of 5 nm are fabricated and characterized from room temperature (RT) down to 5.5 K. Thanks to the improved electrostatics by the scaled NW and 3D GAA structure, close to ideal transfer characteristics are obtained at both RT and 5.5 K with a sharp switching. Benefiting from less defects in Si created by the implantation into silicide (IIS) process, the band tail effects and neutral defects scattering are suppressed. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…b) Cross section of a gate-all-around silicon nanowire FET with a gate length L ¼ 70 nm and 4 nm HfO 2 gate dielectric. [45] 10 -11 10 -10 10 -9 10 -8 10 -7 10 -6 10 -5 I d (A/μm) temperatures, the threshold voltage needs to be such that in the off-state the channel represents a potential barrier with a very small height in the few meV range (as illustrated in Figure 1a). Since tunneling depends exponentially on the potential barrier height, cCMOS devices are much more affected by source-drain tunneling as compared to room temperature.…”
Section: Discussion Of Effective Oxide Scalingmentioning
confidence: 99%
See 2 more Smart Citations
“…b) Cross section of a gate-all-around silicon nanowire FET with a gate length L ¼ 70 nm and 4 nm HfO 2 gate dielectric. [45] 10 -11 10 -10 10 -9 10 -8 10 -7 10 -6 10 -5 I d (A/μm) temperatures, the threshold voltage needs to be such that in the off-state the channel represents a potential barrier with a very small height in the few meV range (as illustrated in Figure 1a). Since tunneling depends exponentially on the potential barrier height, cCMOS devices are much more affected by source-drain tunneling as compared to room temperature.…”
Section: Discussion Of Effective Oxide Scalingmentioning
confidence: 99%
“…b) Cross section of a gate‐all‐around silicon nanowire FET with a gate length L = 70 nm $L = 70 \textrm{ } \textrm{ } \text{nm}$ and 4 nm HfO 2 $\left(\text{HfO}\right)_{2}$ gate dielectric. [ 45 ]…”
Section: Switching Behavior Of Cryogenic Mosfetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, CMOS (complementary metal oxide semiconductor) integrated circuits based on silicon have been developed rapidly, due to which transistor's size has entered the 5 nm node, and has become close to the physical limit. [1][2][3][4] Due to the size effect, it is diffficult to follow Moore's Law. 5 To keep the device performance unchanged, the processing of the transistors has been significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the saturation of the critical parameters occurs due to defects and interface traps induced by the source/drain implantation, which play a key role in the band tail effect at deep cryogenic temperatures and prevent the theoretically predicted performance enhancement of the PMOS device. [12][13][14][15][16] It has been shown that SiGe epitaxy can improve the drain current and mobility of FD-SOI devices by introducing strain at cryogenic temperatures. 14,17 In addition, the utilization of a silicide metallic source/drain results in dopant segregation through the implantation into the silicide (Silicide As Diffusion Source, SADS).…”
mentioning
confidence: 99%